At the Limits of Cure - Venkat, Bharat Jayram (Duke University Press, 2021)
Drawing on historical and ethnographic research on tuberculosis in India, Bharat Jayram Venkat explores what it means to be cured and what it means for a cure to be partial, temporary, or selectively effective.